The Combination of RTE Model with PQ4R Strategy to Improve Student Mathematics Learning Outcomes - Nurul Zahrotil Imania; Fury Styo Siskawati; Sholahudin Al Ayubi (Universitas Islam Jember, 2019)
Learning is the main activity in the education process. Based on the observations made, about 60% of students obtained a value of ≤ 70. This study aims to improve the efficiency and student learning outcomes in materials related to the RTE model with the PQ4R strategy. This type of research is classroom action research (CAR). The research procedure used used 2 cycles with 2 times of learning and 1 cycle end of each test in each cycle. Based on the results of the study, the percentage of student learning activities in the first cycle was 73.44% and the second cycle was 90%. While the results of student tests in the first cycle obtained an average value of 67.16 while in the second cycle amounted to 77.87. This proves that student activities and learning outcomes can be improved by applying the RTE learning model with the PQ4R Strategy. This collaborative model is used to release boredom in the activity of learning. Keywords: RTE, PQ4R, Learning Outcomes